Perbaikan Rute Distribusi Cabai dengan Pendekatan Algoritma Dijkstra di Kota Medan - Situmorang, Ika Verawasty; Sembiring, Anita Christine (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The shortest track is the shortest track used to get from a place to a destination. In general, road users logically choose the road with the shortest route to avoid distance, time and expensive costs. The problem in this study is the problem of chili distribution which will be distributed to several markets in the city of Medan according to the market demand that is passed. The problem of the shortest route is a very interesting thing to discuss in human life so that in carrying out activities becomes more optimal by calculating the distance between nodes and later it will be a solution that will be used to find the opimal distance that must be traveled. One of the solutions that will be applied in this study is by utilizing one of the methods, namely the Dijkstra Algorithm. The Dijkstra algorithm is a method used to determine the shortest distance from the origin node of the destination node that passes through several nodes or places. So that by using the Dijkstra Algorithm, route improvements are obtained, namely the point that must be passed by the distributor so that the cost is more optimal in distributing chili, namely through the X-B-C-D-E-F-G-H point with a distance that must be traveled, which is 27 km. This route is the optimal result in carrying out chili distribution.